PENGOLAHAN MINYAK GORENG BEKAS (JELANTAH) SEBAGAI PENGGANTI BAHAN BAKAR MINYAK TANAH (BIOFUEL) BAGI PEDAGANG GORENGAN DI SEKITAR FMIPAUNNES - Setyaningsih, Natalia Erna; Wiwit, Wasi Sakti (Universitas Negeri Semarang, 2017)
Cooking oil is one of the needs of society in order to fulfill daily needs. The economic condition of Indonesian people is very diverse, some use cooking oil for single use but some also use cooking oil for several times usage. The high unsaturated fatty acids in cooking oil, cause cooking oil will be easily damaged in the process of frying (deep frying) because in the process of frying, oil will be heated continuously at high temperatures. The use of used cooking oil or jelantah can cause adverse effects to the commu- nity and the environment. The adverse impacts on the community are caused by the decline in the quality of food fried with cooking oil which results in disruption of public health. Adverse impact to the environment is the disposal of cooking oil without first processing can pollute the soil and water environment. Utilization of used cooking oil as kerosene replacement fuel is one solution that can be tak- en when facing the bad impact of used cooking oil. In order to serve as a substitute fuel for kerosene, jelantah oil must have karaketristik that is almost the same as kerosene. One of the most important characteristics is the viscosity number. Wrinkled oil has a high viscosity, so that the use of jelantah oil must undergo certain processes to decrease its viscosity. One way to reduce viscosity is by warming at high temperatures over long periods of time. Partners in this devotional activity are the vendors of gorengan around the campus of UNNES FMIPA. They use a lot of cooking oil in their business, maybe even cooking oil used many times and waste of used cooking oil will be thrown indiscriminately so as to pollute the surrounding environment. With this devotion is expected the traders gorengan around FMIPA UNNES campus can process waste used cooking oil into fuel substitute kerosene so that will reduce environmental pollution.